SAFETY DESIGN AERONAUTICAL ENGINEERING - Tamargazin, Aleksandr; Linnik, Ivan (Proceedings of National Aviation University (archive), 2012)
The article deals with contemporary issues of safety of aircraft structures, which are fundamental in the choice of approaches to the continuing airworthiness of aircraft which re fundamental in the choice of approaches to continuing airworthiness of aircraft. The features of the formation methods of technical maintenance of aircraft in view of the design type are considered. Experience of aircraft maintenance has shown that the use of combined operational vitality in a number of cases has helped to prevent the catastrophic destruction of aircraft at a time when high enough qualifications for airline personnel were not satisfied.